MMP20 Proteolysis of Native Amelogenin Regulates Mineralization In Vitro. (December 2016) - Kwak, S.Y.; Yamakoshi, Y.; Simmer, J.P.; Margolis, H.C.
Recent studies have shown that native phosphorylated full-length porcine amelogenin (P173) and its predominant cleavage product (P148) can inhibit spontaneous calcium phosphate formation in vitro by stabilizing an amorphous calcium phosphate (ACP) precursor phase. Since full-length amelogenin undergoes proteolysis by matrix metalloproteinase 20 (MMP20, enamelysin) soon after secretion, the present study was conducted to assess the effect of amelogenin proteolysis on calcium phosphate formation. Calcium and phosphate were sequentially added to protein solutions without and with added MMP20 (ratio = 200:1) under physiological-like conditions of ionic strength (163 mM) in 50 mM Tris-HCl (pH 7.4) at 37 °C. Protein degradation with time was assessed by gel-electrophoresis, and mineral products formed were characterized by transmission electron microscopy (TEM). MMP20 was found to cleave P173 to primarily generate P148, along with P162, P46-148, and P63/64-148. In sharp contrast, MMP20 did not cleave P148. In addition, the formation of well-aligned bundles of enamel-like hydroxyapatite (HA) crystals was promoted in the presence of P173 with added MMP20, while only ACP particles were seen in the absence of MMP20. Although P148 was found to have a somewhat lower capacity to stabilize ACP and prevent HA formation compared with P173 in the absence of MMP20, essentially no HA formation was observed in the presence of somewhat higher concentrations of P148 regardless of MMP20 addition, due to the lack of observed protein proteolysis. Present findings suggest that ACP transformation to ordered arrays of enamel crystals may be regulated in part by the proteolysis of full-length native amelogenin, while the predominant amelogenin degradation product in developing enamel (e.g., P148) primarily serves to prevent uncontrolled mineral formation during the secretory stage of amelogenesis.